2015
DOI: 10.1590/0004-282x20150088
|View full text |Cite
|
Sign up to set email alerts
|

Relative luminosity in the plus maze upon the exploratory behaviour of female Wistar rats

Abstract: Animal models have played an important role in furthering our understanding of complex biological basis and mechanisms underlying the pathogenesis of human anxiety. They have also contributed to the provision of preclinical models that enable the discovery and screening of new potential therapeutical drugs 1 . Moreover, animal models of anxiety have been considered as an invaluable approach, since animals display similar autonomic and behavioral reactions during anxiety states 2,3,4,5 . The present research ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
3
0
2
Order By: Relevance
“…Once the estrous cycle is taken into account, the picture starts to become less clear. In rats, some investigators report reduced anxiety levels (i.e., a more time spent in the open arms of the maze) in proestrus/estrus compared to diestrus ( 16 18 , 40 , 64 70 ) whereas others fail to see estrous cycle-linked effects at all ( 16 , 19 , 61 , 71 73 ). However, not all workers compare all stages of the cycle and in some cases results from two stages of the cycle have been pooled, which makes direct comparison between studies difficult.…”
Section: Animal Models Of Anxiety—behavior Of Females In Male Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Once the estrous cycle is taken into account, the picture starts to become less clear. In rats, some investigators report reduced anxiety levels (i.e., a more time spent in the open arms of the maze) in proestrus/estrus compared to diestrus ( 16 18 , 40 , 64 70 ) whereas others fail to see estrous cycle-linked effects at all ( 16 , 19 , 61 , 71 73 ). However, not all workers compare all stages of the cycle and in some cases results from two stages of the cycle have been pooled, which makes direct comparison between studies difficult.…”
Section: Animal Models Of Anxiety—behavior Of Females In Male Modelsmentioning
confidence: 99%
“…In males, many factors have been identified that can influence responding and potentially lead to inconsistencies between results from different laboratories due to methodological differences. The importance of recognizing and carefully controlling testing conditions, particularly light level, has been highlighted ( 73 , 77 , 78 ). The age of the rat, circadian phase and light illumination level during testing have all been reported to influence the behavior of males ( 77 , 79 84 ) but see ( 85 ) for an opposing view.…”
Section: Animal Models Of Anxiety—behavior Of Females In Male Modelsmentioning
confidence: 99%
“…Thus, we believe that the effects on the locomotion of females may have been related to the natural oscillation of sexual hormones, although we do not exclude the increased anxiety level to some extent, because of the novelty of the environment. For instance, female rats tend to exhibit greater locomotion in novel environments when compared to males in tests such as the open field and EPM (Johnston et al , 1991; Fernandes et al , 1999; Simpson et al , 2012; Sakae et al , 2015). Although we did not examine, in this study, the modulation of ovarian hormones and the control of the estrous cycle, for example.…”
Section: Discussionmentioning
confidence: 99%
“…Em revisão recente, Lovick e Zangrossi (2021) abordaram com mais detalhes essa questão. Por exemplo, no LCE alguns trabalhos mostram não haver diferenças entre as fases do ciclo (FERNÁNDEZ-GUASTI et al, 1999;MOLINA-HERNÁNDEZ et al, 2013;NIN et al, 2012;SAKAE et al, 2015;SANTOS et al, 2014;SCHOLL et al, 2019), É digno de nota que em nosso estudo, células serotonérgicas não foram ativadas pelo desafio de hipóxia. Estudos realizados em machos também mostram um nível muito baixo, ou mesmo a ausência de expressão de c-Fos em células serotonérgicas de alguns subnúcleos do NDR após diferentes desafios estressantes (BARATTA et al, 2018;LOPES et al, 2016;ROCHE et al, 2003;SPANNUTH et al, 2011;VILELA-COSTA et al, 2019).…”
Section: Experimento 3: Efeitos Da Administração Aguda E Sistêmica De...unclassified